Heterozygotes for ACAN dwarfism alleles in horses have reduced stature. (17th February 2020) - Graves, K. T.; Eberth, J. E.; Bailey, E.
Summary: Homozygous and compound heterozygous Miniature horses for ACAN alleles D1, D2, D3* and D4 exhibit chondrodysplastic dwarfism (OMIA 001271‐9796). In a previous study, the carrier rate for these four alleles, combined, was 26.2%. The purpose of this study was to investigate whether carriers of these dwarfism‐causing alleles had a shorter withers height than non‐carriers. A total of 245 Miniature horses were tested for these four ACAN alleles and also were measured for withers height. Of these horses, 98 were carriers and 147 were non‐carriers. A statistically significant difference of 1.43 inches was observed with the carriers being shorter ( P = 1.72E − 11). The range of heights for the two groups overlapped, indicating that other factors, including genes, have an impact on withers height. However, the high carrier rate of these dwarfism‐causing variants may be due to selection for decreased height.